Electrochemical Capacitance DNA Sensing at Hairpin-Modified Au Electrodes. (11th August 2011) - Rivera-Gandía, Joel; del Mar Maldonado, Maria; De La Torre-Meléndez, Yarimar; Ortiz-Quiles, Edwin O.; Vargas-Barbosa, Nella M.; Cabrera, Carlos R.
Abstract : An interfacial capacitance measurement electrochemical technique has been used for the sensing of self-assembled DNA hairpin probes ( M. tuberculosis and B. anthracis ) attached to Au electrodes. The double-layer capacitance (C dl ) was determined with electrochemical perturbations from 0.2 V to 0.5 V versus Ag/AgCl at a Au/ M. tuberculosis DNA hairpin probe at surface coverage Au electrodes. The capacitance study was done at pH 7, which was necessary to maintain the M. tuberculosis and B. anthracis DNA probes closed during the electrochemical perturbation. Detailed experimental analysis carried out by repetitively switching the electrochemical potential between 0.2 and 0.5 V (versus Ag/AgCl) strongly supports the use of capacitance measurements as a tool to detect the hybridization of DNA targets. A large change in the capacitance deference between 0.2 and 0.5 V was observed in the DNA hybridization process. Therefore, no fluorophores or secondary transducers were necessary to sense a DNA target for both DNA hairpins.